Design and Implementation of EEG Signals Analysis on FPGA (International Journal of Engineering and Computer Science, 2017)
In today’s world our life style accumulates too much of stress. This stress is major factor for deteriorating health. To reduce the stress level, meditation is one of the ways. The Electroencephalography (EEG) is characterized by five signals they are Alpha, Beta, Gamma, Delta and Theta.  This paper focuses on the analysis of EEG signals of meditating and non-meditating persons. The signals are analyzed using Matlab and Verilog Xilinx 14.7 on FPGA. It was found that the variation of alpha wave in a person who is meditating regularly was less and delta wave density is more compared to a person who is not meditating